Pengaruh Good Corporate Governance terhadap Manajemen Laba oleh CEO Baru pada Perusahaan Manufaktur - Widianjani, Ni Putu; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 30 No 1 (2020)DO - 10.24843/EJA.2020.v30.i01.p19, 2020)
CEO turnover in a company is a certain activity. At the turn of the CEO many possibilities can occur, one of which is earnings management practices carried out by the new CEO. Earnings management practices can be avoided with good corporate governance. Manufacturing companies were the sectors of the IDX in the 2013-2017 period selected as the study population. Samples obtained as many as 36 samples will then be processed using multiple linear regression. This sample was obtained through selection criteria, namely by purposive sampling technique. The results obtained are good corporate governance has a negative effect on earnings management. Keywords: Good Corporate Governance, Earnings Management, CEO Turnover